A note about isothermic surfaces in Rn-j,j - M. P. Dussan; M. A. Magid (Revista Integración, 2008)
In this note we survey our results on the description of ti- melike isothermic surfaces in Rn−j,j using the Grassmannian systems or U/K-systems. We give the natural extensions of the definition of Ribaucour and Darboux transformations for timelike isothermic surfaces and review how those transformations correspond to dressing actions of suitable simple elements.